2016
DOI: 10.14310/horm.2002.1662
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of type 2 diabetes mellitus in a Greek adult population

Abstract: the prevalence of diabetes mellitus (dM) is increasing worldwide reaching epidemic proportions. the aim of the present study was to estimate the prevalence of dM in thessaly, a large region of central Greece, and to extrapolate our results to the population of the entire country. A random sample of 805 adults (421 females and 384 men) living in thessaly, aged 18-80 years, was surveyed. After completing a questionnaire about health status and a thorough physical examination, a blood sample was obtained from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In the Thessaly study [8], the incidence in the 70-80 age group was 37.5%, while in the 40-49 age group it was only 8.37%. The reduction in the mortality of diabetic individuals due to better access to medical care is also a fact.…”
Section: Possible Explanation Of the Increase Of Dm Casesmentioning
confidence: 91%
See 3 more Smart Citations
“…In the Thessaly study [8], the incidence in the 70-80 age group was 37.5%, while in the 40-49 age group it was only 8.37%. The reduction in the mortality of diabetic individuals due to better access to medical care is also a fact.…”
Section: Possible Explanation Of the Increase Of Dm Casesmentioning
confidence: 91%
“…The study of Thessaly region by Koukoulis et al [8] concerns the period [2003][2004][2005]. It involved carrying out glucose measurements, and additionally performing an OGTT, which further increased the sensitivity of the study and therefore higher prevalence rates are expected.…”
Section: Methodology Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between T2DM risk and additional metabolic syndrome components (e.g. hypertension and dyslipidemia) has been also investigated in various European studies [22,24,34]. As such, data from studies in Italy and Greece showed 2-to 3-fold higher T2DM incidence in patients with hypertension (systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg or treatment for hypertension) compared to normotensive individuals, further indicating that hypertension is independently associated with higher T2DM risk [22,24].…”
Section: Other Metabolic Syndrome Componentsmentioning
confidence: 99%